Strategi Kepala Sekolah dalam Meningkatkan Profesionalisme Guru dan Tenaga Kependidikan di SDN Pagu 2 Kecamatan Wates Kabupaten Kediri - Lumiati, Aning; Hertanto, Arip; Mindar Setianingsih, Dewi; Karwanto, Karwanto; Rifqi, Ainur (Politeknik Penerbangan Surabaya, 2025)
This study aims to reveal and analyse the strategies implemented by the principal in improving the professionalism of teachers and educational staff at SDN Pagu 2, Wates District, Kediri Regency. This study employs a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The results indicate that the school principal actively designs various strategies for human resource development and training at the school. These strategies include academic supervision, facilitating teacher and educational staff training, strengthening a collaborative work culture, and enhancing work motivation through a personalised approach. The main challenges faced include limited funding, restricted access to external training, and insufficient active participation from some educational staff. The study concludes that the principal's adaptive and contextual strategies play a crucial role in enhancing professionalism within the elementary school environment.